2020
DOI: 10.1002/app.49012
|View full text |Cite
|
Sign up to set email alerts
|

Highly robust and transparent flexible cover window films based on UV‐curable polysilsesquioxane nano sol

Abstract: Flexible cover window films based on the ultraviolet‐curable polysilsesquioxane are prepared to have enhanced mechanical, optical properties, and bending performance. To figure out the factors determining those properties, post–treatment conditions are varied into the light source, temperature, and relative humidity. Then, the effect of such variables is examined in respect of surface hardness, yellow index (YI), and bending cycle reliability of flexible hard coating. Also, the effect of photoinitiator type in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The OH and Si–H bonds disappear with the formation of Si–Si bonds because the EB breaks the Si–H bonds and converts them into free radical states. The suspended silicon atoms then recombine into Si–Si bonds. The other change in the silicon-containing functional groups after EB curing is the change in the Si–OH bonds to Si–O–Si bonds . Moreover, it can be seen in Figure c,d that the EB-cured colloidal siloxane coating layer further affects carbon-containing groups.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OH and Si–H bonds disappear with the formation of Si–Si bonds because the EB breaks the Si–H bonds and converts them into free radical states. The suspended silicon atoms then recombine into Si–Si bonds. The other change in the silicon-containing functional groups after EB curing is the change in the Si–OH bonds to Si–O–Si bonds . Moreover, it can be seen in Figure c,d that the EB-cured colloidal siloxane coating layer further affects carbon-containing groups.…”
Section: Results and Discussionmentioning
confidence: 99%
“…These curing methods enhance the hardness of coating materials, yielding better folding performance. Traditional thermal curing increases the hardness by changing the distribution of Si–O and Si–H bonds via chemical changes in the material . However, long curing times, high energy consumption, complicated processes, and insufficient heat penetration depths restrict the application of thermal curing for hard coating.…”
Section: Introductionmentioning
confidence: 99%
“…When a polysilsesquioxane solution is coated on a substrate and then cured, a cross-linked gel film is formed. By taking advantage of their excellent mechanical and thermal stability and transparency, polysilsesquioxanes have been applied as a scratch-resistant coating, , barrier coating, , optical film, , and low dielectric film. Additionally, owing to their thermal stability and nonflammable property, the cross-linked gel film of polysilsesquioxanes may be utilized as thermal barrier coating under high-temperature conditions. Polysilsesquioxane also exhibits good processability for coating, which could be exploited for the fabrication of thermal barrier coating on various substrates and materials by spin coating, dip coating, or spray coating.…”
Section: Introductionmentioning
confidence: 99%
“…In general, acid-catalyzed reactions are used to synthesize linear polymers and branched polysiloxanes, and base and heating reactions are widely used to synthesize cubes and ladder-like silsesquioxanes (LPSQs) [ 21 ]. Recently, silsesquioxane structure based on 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (ECTMS), which has high thermal stability and good mechanical properties, has been widely studied [ 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a siloxane hybrid structure was synthesized using ECTMS by Bae et al that showed a 9H pencil hardness at a load of 9.8 N (coating thickness of 50 μm) and an 88.5% elastic recovery value [ 40 ]. Jeong et al reported that polysilsesquioxane with ECTMS was flexible even in a folding test repeated 100,000 times at a radius of curvature of 3 mm [ 41 ].…”
Section: Introductionmentioning
confidence: 99%